INVESTMENT FEASIBILITY STUDY ON EXPANSION OF BUSINESS TO INCREASE THE NUMBER OF PRODUCTION (Case Study on Tile Company Expansion Press Sokka Super KBR, in Godean Yogyakarta) - Mulyani, Dwi; Lastari, SE., MM, Siwi (Management, 2010)
This study intends to assess investment proposals in the form of additions of fixed assets is one Tobong units and one unit of transport vehicles (trucks) and working capital pemanbahan based on market aspects, technical aspects and financial aspects. The results of this analysis will eventually be used as guidelines for the management (decision makers) to make a decision whether the investment proposal is acceptable and feasible Data used in this research is data sales volume in 1999 until 2003 and investment value. Data collection methods used were interviews, observation and documentation. The data analysis technique used is the method of evaluating the profitability of investment that is a pay-back period and net present of value. Results of data analysis based on sales volume from 1999 to 2003 states that the valuation based on market aspects, in 2004 until 2008 showed an estimated increase in demand, so that its market share which will be controlled by 30%, demonstrating the company´s strong position in competition with other companies. Technical aspects indicate that the infrastructure is owned by the company was still able to produce at levels greater output, then the maximized production capacity to 600,000 units per year. The addition of one unit and one unit Tobong transport vehicles are needed to support the success in meeting consumer demand. Assessment of the investment plan based on financial aspects indicate that the long payback period that is embedded in the investment (pay-back period) is 3 years 1 month and 24 days were positive NPV indicates that this figure is a condition of acceptable and worthy of investment. From all these aspects, the investment company´s business expansion in tile press